The Effect of Accounting Literacy and Risk Management on the Financial Performance of BRILink Agents through Operational Efficiency - Nargis Aprillianti; Mahmud Mahmud; Fahrudin Fahrudin (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the impacts of accounting literacy and risk management on the financial performance of BRILink agents, evaluating the mediating role of operational efficiency. Research Method: Using a quantitative cross-sectional design, data were collected via structured questionnaires from 70 micro-banking agents in Dompu Regency through stratified proportionate random sampling and analyzed using PLS-SEM. Results and Discussion: Accounting literacy significantly improves both operational efficiency and financial performance. Conversely, risk management has no direct effect on financial performance but strongly drives operational efficiency. Crucially, operational efficiency partially mediates accounting literacy and fully mediates risk management's impact on financial performance. Implications: Banking institutions and regulators should develop agent training modules that integrate agile, low-cost operational workflows rather than focusing solely on basic bookkeeping to mitigate transaction errors and cash leakage. Originality: This research establishes a novel operational mediation model for branchless micro-banking in remote regions, demonstrating that cognitive and preventive capacities require high operational efficiency to yield financial returns.